An analysis of mathematical connection ability viewed from students’ questioning-skills through the educational tools in connected mathematics project learning model - Hidayah, Isti; Meiliana, Dwi Kurniaasih; Rochmad, Rochmad (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aimed to determine the 7th grade students’ mathematical connections ability through CMP learning models to achieve learning mastery; to know whether the 7th grade students’ mathematical connections ability through CMP learning model was better than CMP learning model without educational tools; to know the student's questioning-skill factors; and to know the description of the ability of mathematical connections viewed from the 7th grade students' questioning-skills through the CMP learning model. The research method used was mixed method of the concurrent embedded model. The population in this research were all 7th-grade students of SMP Negeri 3 Semarang. The sample of research was taken from 7D and 7F classes. Subjects of this study were as many as 6 subjects with each of 2 subjects chosen from each category of questioning-skills. The results of the research showed that students' mathematical connection ability through the educational tools in CMP model learning achieved learning mastery; students' mathematical connection ability through CMP learning model was better than CMP learning model without the educational tools; the factors that influenced the students' questioning-skill were willingness within students, the use of educational tools, project-based learning/problem, and the response given by the teacher when students asked; and students' mathematical connection ability through CMP learning model viewed from questioning-skills indicated that students with high questioning-skill had best mathematical connection ability, followed by students with medium questioning-skill, and low questioning-skill.